2001
DOI: 10.1037/0022-006x.69.3.440
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of weight control and weight control plus body image therapy for obese men and women.

Abstract: Participants were 65 obese men and women who were randomly assigned to either weight control or weight control plus cognitive behavioral body image therapy. Both conditions showed clinically significant improvements in body image at posttreatment and 1-year follow-up. Adding body image therapy to weight control did not result in greater psychological improvements and did not result in better maintenance of body image change when participants regained weight after treatment. Weight loss and maintenance were equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 25 publications
4
71
0
4
Order By: Relevance
“…But other studies found disagreeing findings and reported overestimation of body size by obese people in general. 21,22 The fact that those drawings reported as desired were largely within lower ranges of BMI compared to those reported as current BMI is suggestive of body image dissatisfaction, showing that both men and women praise thinness ideals. The appreciation of thinness in modern societies, of bodies so lank unattainable for most people, creates a condition of everlasting dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…But other studies found disagreeing findings and reported overestimation of body size by obese people in general. 21,22 The fact that those drawings reported as desired were largely within lower ranges of BMI compared to those reported as current BMI is suggestive of body image dissatisfaction, showing that both men and women praise thinness ideals. The appreciation of thinness in modern societies, of bodies so lank unattainable for most people, creates a condition of everlasting dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This view was similarly echoed in a report of the House of Commons Health Committee in 2004. 37 More recently a survey by the Dr Foster organisation published in 2005 40 showed that primary care organisations employ a number of innovative approaches to the management of obesity; however, there is considerable national and regional variation in the service provided. The survey also showed that while more organisations had established weight management clinics than in their previous survey in 2003 (up by 5%), in the majority of general practices (69%) there was still no organised weight-management clinic.…”
Section: Variation In Servicesmentioning
confidence: 99%
“…Three sessions per week (non-consecutive days) for first 28 weeks, two per week during weeks [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. 12 minutes at week 1, additional 2 minutes to routine each week, by week 14 performed 40 minutes of stepping During weeks 29-48 they were assisted in developing at home exercise to replace the third exercise session deleted from their supervised training Delivered: graduate students in exercise physiology who followed structured protocols Level of supervision: all sessions were supervised (no further detail given)…”
Section: Exercisementioning
confidence: 99%
“…É reconhecido o papel da insatisfação com a própria imagem corporal nos distúrbios alimentares e na produção do estresse característico da vida moderna, outro importante fator sociocultural associado ao quadro de morbimortalidade atual (Cash, 2004;Madrigal & cols., 2000;Ramirez & Rosen, 2001;Smolak, 2004). Lynch, Heil, Elise e Havens (2008) demonstraram que a insatisfação corporal em adolescentes americanas era o mediador de maior significância entre o Índice de Massa Corporal (IMC) e o risco de transtorno alimentar e comportamentos alimentares de risco à saúde.…”
unclassified